The Maltese Archipelago at the dawn of history : reassessment of the 1909 and 1959 excavations at Qlejgha tal-Bahrija and other essays - Tanasi, Davide, 1974-; Cardona, David (Archaeopress Archaeology, 2020)
This collection of essays provides a reassessment of the multifaceted evidence which emerged from excavations carried out in 1909 and 1959 in the settlement of Bahrija, both largely unpublished until now. Bahrija is a key site for understanding the later stages of Maltese prehistory before the beginning of the Phoenician colonial period.